Conceptualizing Research Trends of the Digital Economy (1998 – 2024) Evidence from Bibliometric Analysis - Anggreni, Melysa; Kurnianingtyas, Hana Yulia; Shafira, Ladinda Diaz; Apriyanto, Anggito Abi (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
The existence of the digital economy brings novelty to global economic activities, through technological transformation that continues to grow rapidly from year to year. This research focuses on conceptualizing the development trend of digital economy research publications from 1998 – 2024 by looking at publication trends, annual publication growth rates, recent publications, most relevant sources, and country contributions to publications. In addition, this study also aims to provide information on the relevance of keywords needed in digital economy research in the future. This research took the Scopus database of 1,177 documents and used bibliometric analysis with a descriptive approach. The researchers also used R Studio tools to obtain key information and VOSviewer to conduct a thorough analysis. The results of the analysis show that the growth of literature has increased significantly since 2016 and shows a positive trend. Recent publications on the digital economy are dominated by articles written by Wang Y. Keyword analysis shows that the focus of digital economy research is interrelated with 4 main clusters, namely; innovation, economic growth, digital technology, and China as a country that dominates research contributions on the topic of digital economy. The data visualization results also present how the focus of research trends over the past 5 years. With the focus of research in 2020 – 2022, namely on innovation, digital economy, economic growth and things that lead to digitalization. Post-pandemic, the focus of research has shifted slightly to addressing problems caused by environmental damage. With a research focus on digitalization and green innovation.